Survei Penyakit Kecacingan Pada Pekerja Tambang Tradisional di Desa Soyoan Kecamatan Ratatotok Kabupaten Minahasa Tenggara - Tuuk, Herlisa A.V.; Pijoh, Victor D.; Bernadus, Janno B.B. (Universitas Sam Ratulangi, 2020)
Abstract: Helminthiasis is an infection that generally occurs in humans and is often caused by worm parasites, specifically intestinal nematodes, that are transmitted into the body through soil or so-called Soil Transmitted Helminths (STH). Traditional miners are at high risk to suffer from helminthiasis caused by STH due to frequent contact with soil. Soyoan Village was chosen based on an initial survey. It was found that the majority of its population are traditional gold miners. Most mining activities still use simple safety equipment, along with poor sanitation in the area and miners having frequent contact with the ground. If the helminthiasis is left alone, in addition to causing anemia and malnutrition, it can also cause workloads that inhibit concentration, a decrease in work ability and eventually death. This study to identify helminthiasis in traditional mining workers. A total of 16 miners (18%) out of 86 miners suffered from helminthiasis. All positive samples were infected by STH, specifically hookworm. The highest number of respondents were male with a number of 85 people (99%), and there was only 1 female (1%). Most respondents were in the age group of 26-35 with a total of 27 people (31%). A total of 16 respondents (18%) had helminthiasis infection caused by STH, specifically hookworm. In conclusion, helminthiasis prevalence is still relatively low, so disease control can still be done easily.Keywords: Helminthiasis, traditional miners Abstrak: Kecacingan merupakan infeksi yang umumnya terjadi pada manusia dan paling sering disebabkan oleh parasit cacing jenis nematoda usus yang ditularkan ke dalam tubuh melalui tanah atau disebut Soil Transmitted Helminths (STH). Profesi penambang tradisional termasuk kelompok beresiko tinggi mengalami infeksi kecacingan yang disebabkan oleh STH karena sering berkontak dengan tanah. Desa Soyoan dipilih berdasarkan survei awal, didapatkan bahwa mayoritas penduduknya adalah penambang emas tradisional. Aktifitas pertambangan kebanyakan masih menggunakan alat pengaman diri seadanya, sanitasi yang buruk dan sering berkontak dengan tanah. Apabila infeksi kecacingan dibiarkan maka selain menyebabkan anemia, dan malnutrisi juga dapat menimbulkan beban kerja yang membuat konsentrasi terhambat, terjadinya penurunan kemampuan kerja sampai kematian. Penambang yang mengalami infeksi kecacingan sebanyak 16 orang (18%) dari 86 sampel subyek penelitian. Semua sampel yang positif terinfeksi oleh cacing STH jenis cacing tambang. Jumlah responden terbanyak berjenis kelamin laki-laki sebanyak 85 orang (99%) dan jenis kelamin perempuan 1 orang (1%), responden terbanyak berada di kelompok usia 26-35 tahun sebanyak 27 orang (31%). Sebanyak 16 orang responden (18%) yang mengalami infeksi kecacingan oleh cacing STH jenis cacing tambang. Simpulannya ialah prevalensi kecacingan masih tergolong rendah sehingga pengontrolan penyakit masih dapat dilakukan dengan mudah.Kata kunci : Kecacingan, pekerja tambang tradisional